2000
DOI: 10.1021/jo0002036
|View full text |Cite
|
Sign up to set email alerts
|

Singly Bridged Calix[8]crowns

Abstract: Crowned calix[8]arenes are obtained by direct alkylation of p-tert-butylcalix[8]arene (1) with poly(ethylene glycol) ditosylates in the presence of various bases. K2CO3 promotes the preferential formation of 1,3-calix[8]crowns. Cs2CO3 mainly gives the 1,5-isomers, which are selectively obtained in high yields when shorter chains are used (1,5-crown-2, 88%; 1,5-crown-3, 78%). NaH affords the 1,4-isomers in yields up to 46%, often as the sole crown derivative, besides unreacted 1. 1,2-Calix[8]crowns are also obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…To overcome this kind of problem, we decided to resort to intramolecular bridging as a very convenient method to shape and preorganize larger calixarene macrocycles. [17,18] Thus, we focused our attention on doubly bridged calix [7]arene derivatives, [10] such as 2 (Scheme 1), in which the presence of two short bridges at the 1,4-and 2,3-positions led to a high level of preorganization and suggested potential applications as molecular hosts in supramolecular chemistry. The 1,4-bridging gives rise to two different tetra-and trimeric subunits in 2 defined by the four alkylated and the three unalkylated phenol rings, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this kind of problem, we decided to resort to intramolecular bridging as a very convenient method to shape and preorganize larger calixarene macrocycles. [17,18] Thus, we focused our attention on doubly bridged calix [7]arene derivatives, [10] such as 2 (Scheme 1), in which the presence of two short bridges at the 1,4-and 2,3-positions led to a high level of preorganization and suggested potential applications as molecular hosts in supramolecular chemistry. The 1,4-bridging gives rise to two different tetra-and trimeric subunits in 2 defined by the four alkylated and the three unalkylated phenol rings, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…32 In fact, regarding the aromatic bridging elements, Neri and coworkers 33 in 2002 reported that the treatment of calix[8]arene 1e with Cs 2 CO 3 as base and aromatic shorts bridges such as ortho-, meta-, or para-bis(bromomethyl)benzene afforded to the 1,5-bridged calix[8]arene derivatives 11d-f ( Figure 10) in high yields (80-90%). Interestingly, the regioselectivity of the bridging reaction of the calix[8]arene macrocycle can be controlled by the reaction conditions and in particular by the base used and by the length and nature of the bridge.…”
Section: Calix[8]arenesmentioning
confidence: 99%
“…Cs 2 CO 3 and NaH are generally used in the synthesis of 1,5-isomer. [4][5][6]17 However, using these bases in the reaction, either calix [8]arene remains unchanged or the products are too complex to be separated. Increasing of K 2 CO 3 to 8 equivalents has no remarkable effect on the distribution of products.…”
Section: Figurementioning
confidence: 99%
“…12 Amidebridged calixarenes can be reduced to calixazacrowns by LiAlH 4 . 13 Recently, we have synthesized a 1,3-diamide bridged calix[6]arene and an asymmetrical 1,3:4,5-doubly bridged derivative by reacting p-tert-butylcalix [6]arene with N,N¢-bis(chloroacetyl)ethylenediamine. 14 As an extension of the above work and to prepare calix[8]azacrown, the reaction of such a reagent and its homologue, N, N¢-bis(chloroacetyl)propylenediamine with p-tert-butylcalix[8]arene was investigated, and 1,5-diamide bridged p-tert-butylcalix [8]arenes and a 1,3:5,7-doubly diamide bridged p-tert-butylcalix[8]arene were obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation